ASSOCIATION BETWEEN SPIRITUAL WELL-BEING AND QUALITY OF LIFE AMONG PATIENTS WITH END -STAGE RENAL DISEASE (Journal of Medical & Health Sciences Review, 2025)
Objective: This study aimed to assess the association between spiritual well-being and the quality of life among end-stage renal disease (ESRD) patients undergoing hemodialysis (HD).Methodology: An analytical cross-sectional study was conducted at two public healthcare settings, the Institute of Kidney Disease and Lady Reading Hospital in Peshawar, Khyber Pakhtunkhwa (KPK). The sample, comprising 377 ESRD patients on a minimum of 6 months of hemodialysis, was selected using consecutive sampling. Data on spiritual well-being and quality of life were collected using the Urdu versions of the Spiritual Well-Being (SWB) scale and Quality of Life (QOL) scale, both with alpha-Cronbach's reliability coefficients of 0.82 and 0.74, respectively. Social and demographic data were also collected.Result: The study revealed a strong positive correlation (0.721, p